Epidemiologic Features of Systemic Vasculitides in the Southeast Region of Brazil: Hospital-Based Survey. (October 2020) - Belem, Joice Moraes Faria Monteiro; Pereira, Rosa Maria Rodrigues; Perez, Mariana Ortega; do Prado, Leandro Lara; Calich, Ana Luisa; Sachetto, Zoraida; Bacchiega, Ana Beatriz Santos; Simil, Fabrícia Fonseca; Pedreira, Ana Luisa; Gazzeta, Morgana Ohira; Dinis, Valquíria G.; Mariz, Henrique Ataíde; et al.
Abstract : Background/Objective: The epidemiology of vasculitis is variable in different geographic areas, and this issue has not been approached in Brazil yet. The objective of this study was to assess the frequency of vasculitis in specialized centers in Brazil. Methods: This cross-sectional study was performed in 9 vasculitis outpatient clinics from 6 different states mainly from the Southeast and the Northeast regions of Brazil between 2015 and 2017. Diagnosis and/or classification criteria for Behçet disease (BD), Takayasu arteritis (TA), giant cell arteritis (GCA), polyarteritis nodosa (PAN), granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), eosinophilic granulomatosis with polyangiitis (EGPA), and cryoglobulinemic vasculitis (CryoVas) were used to include patients with at least 6 months of follow-up in this hospital-based survey. Results: A total of 1233 patients with systemic vasculitis were included from the Southeast region. Behçet disease was the most frequent vasculitis (35.0%) followed by TA (26.4%), GPA (16.2%), PAN (5.8%), GCA (5.8%), EGPA (4.3%), MPA (3.4%), and CryoVas (3.0%). Up to 7.8% of vasculitis patients had a juvenile onset, and the frequency of vasculitides found in children and adolescents was as follows: TA (52.6%), BD (24.7%), GPA (12.4%), and PAN (10.3%). No cases of EGPA, MPA, and CryoVas were diagnosed before the age of 18 years. As a comparator, 103 vasculitis patients were included in the Northeast of Brazil where TA was found in 36.9% and BD in 31.1% of vasculitis cases. No GCA cases were found in the Northeast part of Brazil. Conclusions: Similar to the epidemiology of vasculitis in Asia, BD and TA are the most frequent vasculitis in Southeastern Brazilian referral centers. Abstract : Supplemental digital content is available in the text.